Konkan Kanyal-Characters and performance of a newly discovered goat germplasm of Maharashtra - Verma, N K; Aggarwal, R A K; Dixit, S P; Kawatikar, V S; Dangi, P S; Kaur, Navneet; Mishra, Priyanka; Joshi, B K (The Indian Journal of Animal Sciences, 2012)
This study was conducted on 252 animals of Konkan Kanyal goat population belonging to different sex and age groups existing in the different villages of Kudal, Dodamargi, Malvan, Verungla and Sawantwari tehsils of Sindhudurg district of Konkan region of Maharashtra state of India. The Kanyal goats are mainly reared under free range system. Animals are predominantly black with white marking in a specific pattern, however, brown coat with the similar pattern of white or light brown marking are also available. The average body measurements for height at withers, body length, chest girth, paunch girth, face length, horn length, ear length, tail length were estimated. The body weights of adult male and females were 35.26 and 29.80 under field conditions. The average milk production per lactation was 69.035 liter in a lactation period of 96.199±17.49 days and an average milk production 0.609±0.095 liter/day. Average age at first kidding, kidding interval, twinning were recorded under farm conditions. The meat of Kanyal goats is red with fine and firm fiber. Close housing with raised floor are constructed for these goats. Only about 3.0% mortality was reported hence these are well adapted to the agro-ecological conditions of Konkan region. Based on the unique morphology and performance better than the other nondescript goats of the same area Konkan Kanyal goats can be recommended as a new goat breed of Maharashtra state which can be exploited for improving the other local goats for meat purpose.